ANALISIS SEJARAH DAN REALISASI KURIKULUM 1966 - Kristoforus Bagas Romualdi; Zulkarnain Zulkarnain (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2023)
The 1966 curriculum is one of the curricula that was implemented in Indonesia at the end of the Old Order period. However, there is very little discussion about the existence of this curriculum and it is often overlooked in research on the history of the curriculum in Indonesia. Thus, this study aims to analyze the history and curriculum of 1966 using a historical approach. Results Based on the research, it was revealed that the emergence of the 1966 curriculum which was the 1964 curriculum of the Soekarno era could not reveal the events of the First October 1965 Movement or the G 30S/PKI in the New Order narrative. After the bloody incident, with the power of Supersemar, Suharto tried to abolish the notions of communism and Sukarno's typical Manipol-USDEK, one of which was in the world of education by issuing TAP MPRS No. XXVII/MPRS/1966 as the basis for the 1966 curriculum. However, in practice, there are still many points in the provisions that have not been realized optimally during the 1966 curriculum in force. However, TAP MPRS No. XXVII/MPRS/1966 remains the basis for the development of the 1968 curriculum that came after Suharto became de facto and de jure president.